2004
DOI: 10.1080/02786820490494034
|View full text |Cite
|
Sign up to set email alerts
|

An Aerosol Wind Tunnel for Evaluation of Massive-Flow Air Samplers and Calibration of Snow White Sampler

Abstract: ][Massive-flow air samplers are being deployed around the world to collect aerosol samples for analysis of radioactivity as a result of nuclear tests and nuclear accidents. An aerosol wind tunnel capable of an 1100 rrr' min -I flow rate was built at Lovelace Respiratory Research Institute (LRRI) to test the sampling efficiency of these samplers. This aerosol wind tunnel uses a stationary air blender to enha nce mixing, and therefore it achieves the required uniform distribution of wind speed and aerosol concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Schematic of wind tunnel with measurements in inches. Adapted from Figure 1 of Cheng et al (10) by changing the speed of the blower motor. The wind tunnel was calibrated according to U.S Environmental Protection Agency (EPA) (11) and American National Standards Institute (ANSI) standards.…”
Section: Wind Tunnelmentioning
confidence: 97%
See 2 more Smart Citations
“…Schematic of wind tunnel with measurements in inches. Adapted from Figure 1 of Cheng et al (10) by changing the speed of the blower motor. The wind tunnel was calibrated according to U.S Environmental Protection Agency (EPA) (11) and American National Standards Institute (ANSI) standards.…”
Section: Wind Tunnelmentioning
confidence: 97%
“…(10) The wind tunnel consists of an 11-meter-long circular duct with a diameter of 1.83 m; a stationary air blender (Blender Products, Inc. Denver, Colo.), which creates mixing; a flow straightener; a test chamber; and a blower ( Figure 1). …”
Section: Wind Tunnelmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows the schematic diagram of the Lovelace Respiratory Research Institute (LRRI) large wind tunnel facility employed in this research. This wind tunnel facility has been used in many sampler performance studies for different stationary and personal aerosol samplers (Cheng et al, 2004;Irshad et al, 2006;Zhou and Cheng, 2010), and the results acquired have shown that this wind tunnel can provide reliable experimental data for general aerosol sampler evaluation studies. The LRRI large wind tunnel consists of an 11-m circular duct (1.8 m in diameter), an array of industrial gas mixing blenders (Blender Products, Inc. Denver, CO), a honeycomb flow straightener, a 4.3 m (L) Â 3.7 m (W) Â 3.6 m (H) test chamber, a outflow HEPA filter bank, and a 50-hp motor (Marathon Electric, Wausau, WI).…”
Section: Wind Tunnelmentioning
confidence: 96%
“…The collection efficiency and capture efficiency acquired from the tests were also used as indices for evaluating the design features such as the recirculated liquid in both samplers. The evaluation tests were conducted in a large wind tunnel facility (Cheng et al, 2004), and the personal bioaerosol samplers were mounted on an adult manikin to mimic the sampling scenario of a moving person wearing a personal sampler. The aspiration efficiency acquired was compared with the ACGIH inhalable convention (ACGIH 1985), and the effects of the sampling orientation, wind speed, and aerosol size on the aspiration efficiency were investigated as well.…”
Section: Introductionmentioning
confidence: 99%